Preliminary evaluation of a culturally adapted CBT-based online programme for depression and anxiety from a lower middle-income country. (26th November 2021) - Latif, Madeeha; Awan, Falahat; Gul, Mirrat; Husain, M. Omair; Husain, M. Ishrat; Sayyed, Kumail; Magsi, Taj; Naz, Saiqa; Aylem, Ozlem; Phiri, Peter; Irfan, Muhammad; Ayub, Muhammad; et al.
Abstract: Online cognitive behaviour therapy (CBT), self-help and guided self-help (GSH) interventions have been found to be efficacious and cost-effective for treatment of anxiety and depression, but there are limited data from low- and middle-income countries on culturally adapted digital interventions for these common mental disorders. The aim of this study was to investigate the feasibility and acceptability of an online culturally adapted CBT-based guided self-help (CaCBT-GSH) for patients with anxiety and depression in Pakistan. This randomized controlled trial recruited 39 participants from primary care in Karachi, Pakistan and randomized them to two groups. The intervention group received seven modules of CaCBT-GSH plus treatment as usual (TAU) over 12 weeks. The control group was a waitlist control plus TAU. The primary outcomes were feasibility and acceptability. Clinical outcomes included results from the Hospital Anxiety and Depression Scale (HADS) and the WHO Disability Assessment Schedule 2 (WHODAS 2). Assessments were carried out at baseline and at 12 weeks. All 39 individuals who met eligibility criteria for the study agreed to participate. Adherence to the intervention was excellent, with 85% (17/20) completing more than five modules. Statistically significant improvements were found in all clinical outcomes in the intervention group. This was the first trial of an online CaCBT-GSH intervention, which was found to be feasible and acceptable to Pakistani patients with anxiety and depression. CaCBT-GSH may help improve symptoms, depression, anxiety and overall functioning in this population. The results provide rationale for a larger, confirmatory randomized controlled trial of digital CaCBT-GSH. Key learning aims: (1) Leveraging digital and virtual platforms to deliver psychosocial interventions may contribute to addressing the significant treatment gap in low-resource settings. (2) CBT-informed guided self-help is feasible and acceptable in the treatment of common mental disorders in Pakistan. (3) The results of this study merit a larger, appropriately powered confirmatory randomized controlled trial to determine clinical and cost effectiveness.